Work-life balance, time and money: identifying the work-life balance priorities of working class workers - Warren, Tracey (Kluwer, 2017)
This chapter provides an overview of the relative roles played by time and money in debates around work-life balance. It shows how time trumps money in dominant understandings of what ‘work-life’ means and in what parts of our lives are presumed to be in need of balance. Working ‘too many’ hours is seen to be the major challenge for achieving a work-life balance. This is an incomplete account. It is largely about the work-lives of the middle classes and it neglects the priorities of working class workers. The chapter first recaps on the centrality of time within academic work-life debate. It demonstrates how a time-dominant conceptualisation of work-life balance has determined the ways in which balance/imbalance is measured and, similarly, how it shapes policy discourse and development. A serious limitation of this too heavily time-based understanding of work-life balance is that it prioritises the concerns and needs of middle class workers. The study of work-life balance became largely about the problems arising from a ‘time-squeeze’, and potential solutions to it, because it is rooted in analyses of middle class working lives. Accordingly, the work-life needs of working class workers have been neglected by academics and policy makers. Having enough time is indeed core to a balanced work-life. Yet it is not the only ingredient and nor is it one that dominates the narratives of the working class, for whom financial hardship is a serious threat to work-life balancing. If we are to take the work-life needs of working class workers seriously too, it is essential to widen out our understanding of work-life balance in academic debate and policy formulation. It is time for researchers, employers, worker representatives and policy makers to co-produce a more holistic and inclusive work-life balance agenda.